Hydronyms of Klaipėda Region of Unclear Etiology: Ketvergio upalis, Neknupis, Plocis, Rikinė, Župė / Župis - Kregždys, Rolandas (Acta humanitarica academiae Saulensis, 2023)
The article newly actualizes the etymology of the hydronyms Ketvergio upalis, Neknupis, Plocis, Rikinė, Župė / Župis, situated in Klaipėda Region. Given the typology of the indicated morphophonetic changes in the word structure – change of the initial affricate č- to voiceless guttural K-, one can state that the first hydronym belongs to Slavonicisms, i.e., Ketvergio upalis is to be related to Lithuanian substantive četvergas ‘Thursday’. It has been stated that the semantic connotation of the onym is to be based on the etymological analysis of the hydronym Turkupis situated in the Lowlanders area of Raseiniai. It is to be assumed that the primary semmeme of the hydronym Ketvergio upalis should be reconstructed in accordance with the meaning *‘the river flowing near bazaar; noisy river’. The name of the stream Neknupis is interpreted as an authentic factographic relict of the Baltic Lexis. The primary form *Meknupis ‘a stream full of ides’ is reconstructed, i.e., the change of initial consonant *M- is presupposed, cf. N- ← *M- ↔ -n- (due to regressive assimilation). The connotation of the onym is related to the referent ide, as the type of the fish is very typical to the fauna of the stream. The last three hydronyms have been found to be formed of the Germanic words. It is to be assumed that the authentic onyms of Baltic origin were changed with these Germanisms: (1) the onym Plocis (other variants are also possible: Plazis 1912, Plažės ežeras 1994, Plazės gamtinis draustinis 2016, Plačias, Plocė 1959, Pluokis [Pluocis] 1998, Plocė 1959, [German variants] Plotsee, Plazis-Teich, Plazis-See) is related to German hydronym Plötzensee ‘roach lake’ (cf. also German toponyms Plötzenbruch, Plötzbusch, Plötzenhof ↔ Plötzenteich). The primary Lithuanian forms *Plakis ↔ *Plakė ‘roach lake’ are likely to be reconstructed. The authentic Lithuanian hydronym *Plakis in the long run was replaced by Germanism Plocis; (2) etymological analysis of the hydronym Rikinė (Rikio upė) is based on formal identity between morphological cluster -rike used in the West German toponymy and dialectal German substantive, used in East Prussia, Rick ‘a long pole; transverse; pole stuck in the ground; a type of fence’, related to Middle Low German substantive recke / rik ‘a long, thin pole’, rek / rekke ‘fence; a hedge, planted in the middle of the field; grating etc.’, rieke / rikke ‘hedge, quickset’, Middle High German substantive ric, ricke ‘fence, narrow road etc.’ (cf. Old Saxon hydronyms Geld-rike, Lun-rike and toponym Led-rike). The primary Lithuanian forms *Siauroji, *Siaurukė are reconstructed; (3) it is to be assumed that the origin of the hydronyms Župė / Župis (cf. other variants: Szopis, Szopebach, Szob 1725, Szope 1912, 1939), implied by Lithuanian dialectal Germanism zupė ‘soup, mess, skilly’, presuppose the change of the initial consonant, i.e., *Z- → Ž-, typical of the subdialects of Lowlanders. The above-mentioned variants Szopis etc., due to the vocal element -o-, can evidently be related to Middle Low German substantive soppe, sope ‘soup, broth’. The authentic Lithuanian form *Sriuba is reconstructed, cf. hydronym Sriùbupis (from the area of Lowlanders) originated from Lithuanian substantive sriubà ‘pottage; bouillabaisse etc.’.